2021
DOI: 10.3390/ijerph18126202
|View full text |Cite
|
Sign up to set email alerts
|

Comparative UAV Noise-Impact Assessments through Survey and Noise Measurements

Abstract: Possibilities to use unmanned aerial vehicles (UAVs) are rapidly growing. With the development of battery technologies, communication, navigation, surveillance, and autonomous systems in general, many UAVs are expected to operate at relatively low altitudes. Thus, the problem of UAV noise impact on human health and well-being will be more pronounced. In this paper, we conducted noise measurements of two UAVs of different performance (quadrotor and hexarotor) in flying up and down, hovering, and overflight proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Hui et al [ 3 ] investigated the perception (in a subjective, laboratory-based experiment) of a series of drone sounds, accounting for different operating conditions in terms of flight mode and height above the ground. Ivošević et al [ 18 ] carried out a survey where a series of participants reported their in situ subjective assessment on drone noise during a series of drone operations in an open field.…”
Section: Introductionmentioning
confidence: 99%
“…Hui et al [ 3 ] investigated the perception (in a subjective, laboratory-based experiment) of a series of drone sounds, accounting for different operating conditions in terms of flight mode and height above the ground. Ivošević et al [ 18 ] carried out a survey where a series of participants reported their in situ subjective assessment on drone noise during a series of drone operations in an open field.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, UAV technology has improved due to the development of eVTOL and battery technologies. Moreover, autonomous flight for UAVs has been researched due to the development of information and communication technologies (ICT) [8]. Figure 1 indicates the general structure of a UAV.…”
Section: Introductionmentioning
confidence: 99%